Protecting Women’s and Newborns’ Rights in a Public Maternity Unit During the COVID-19 Outbreak: The Case of Dra. Eloísa Díaz - La Florida Hospital in Santiago, Chile - Leiva, Gonzalo; Sadler, Michelle; López, Camila; Quezada, Susana; Flores, Víctor; Sierra, Cristian; Díaz, Susan; Figueroa, Christian (Frontiers in Sociology, 2021)
The Maternity Ward in Dra. Eloísa Díaz hospital, located in the municipality of La Florida, Santiago, Chile, opened its doors in 2014, and has integrated a humanistic model of care called the “Safe Model of Personalized Childbirth” since 2016. With around 4,500 births per year, this hospital has been recognized as an example of excellence in maternity care in the country. The COVID-19 outbreak presented a major challenge: to maintain its quality of care standards despite the health crisis. This article presents this hospital’s maternity care response to the pandemic from March to July 2020, describing the strategies that were deployed and the obstetric outcomes achieved. We carried out semi-structured interviews with midwives and ob/gyns, and a retrospective review of the childbirth standards of care and outcomes of the 55 women who tested positive for SARS-CoV-2. The results show how the maternity's staff responded in ways that avoided negative impacts on the rights of women and newborns. Significant measures taken included the development of protocols to re-establish the labor and birth companion and skin-to-skin contact, which were suspended for almost three weeks at the beginning of the outbreak, and the creation of an Instagram account to communicate with the external community. After some initial weeks of adjustment, the standards of care for all women, including those diagnosed with COVID-19, were re-established almost to their pre-pandemic levels. This case shows that quality of care can be maintained and the rights of women and newborns can be respected during a health crisis, even one as severe as the COVID-19 pandemic.